Evidence-Based Recommendations for the Use of Desidustat in Chronic Kidney Disease - Sourabh Sharma; Bianca Davidson; Dina A Abdellatif; Sanjay Kalra (Journal of the Pakistan Medical Association, 2026)
Anaemia is a common and clinically significant complication of chronic kidney disease (CKD), contributing to reduced quality of life, cardiovascular morbidity, and increased mortality. Conventional management has relied predominantly on injectable erythropoiesis-stimulating agents (ESAs) and iron supplementation; however, these approaches are associated with limitations including hyporesponsiveness, injection burden, and safety concerns. Hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHIs) have emerged as a novel therapeutic class that stimulates endogenous erythropoietin production while improving iron metabolism. Recent Kidney Disease: Improving Global Outcomes (KDIGO) anaemia guidelines acknowledge HIF-PHIs as therapeutic alternatives in selected patients. This review synthesizes available evidence and provides practical, evidence-based recommendations for the use of desidustat across different stages of CKD. Keywords: Chronic kidney disease, Anemia, Desidustat, HIF-PHI, Erythropoiesis, KDIGO.